Ethanol Production from Whey by Kluyveromyces marxianus in Batch Fermentation System: Kinetics Parameters Estimation - Dessy Ariyanti; Hadiyanto Hadiyanto (Bulletin of Chemical Reaction Engineering & Catalysis, 2013)
Whey is the liquid remaining after milk has been curdled and strained. It is a by-product of the manufacture of cheese or casein and has several commercial uses. In environmental point of view, whey is kind of waste which has high pollution level due to it’s contain high organic compound with BOD and COD value 50 and 80 g/L respectively. On the other side, whey also contain an amount of lactose (4.5%-5%); lactose can be used as carbon source and raw material for producing ethanol via fermentation using yeast strain Kluyveromyces marxianus. The objective of this research is to investigate the ethanol production kinetics from crude whey through fermentation using Kluyveromyces marxianus and to predict the model kinetics parameter. The yeast was able to metabolize most of the lactose within 16 h to give 8.64 g/L ethanol, 4.43 g/L biomass, and remain the 3.122 g/L residual lactose. From the results presented it also can be concluded that common kinetic model for microbial growth, substrate consumption, and product formation is a good alternative to describe an experimental batch fermentation of Kluyveromyces marxianus grown on a medium composed of whey. The model was found to be capable of reflecting all batch culture phases to a certain degree of accuracy, giving the parameter value: μmax, Ks, YX/S, α, β : 0.32, 10.52, 0.095, 1.52, and 0.11 respectively.© 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)